AN EFFECT OF COMPENSATION SERVICE CAPABILITIES AND IMPACT ON CUSTOMER SATISFACTION IN PT. BUKOPIN BANK BRANCH MEDAN - Sari, Dian Purnama; Ekawati, Yuni Andri (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This study aims to determine how much influence compensation and service capability together have on customer satisfaction at PT. Bukopin Bank Medan Branch.The population in this study were all employees at PT. Bank Bukopin Branch Medan based on data as of June 2013 as many as 134 people. Data were collected using questionnaires, observation and literature study.Because the calculated F value (0.516) is smaller than F table (3.16), the hypothesis H0 is accepted and the hypothesis H1 is rejected. This shows that statistically the compensation factor and service ability have no significant effect on Customer Satisfaction at PT. Bank Bukopin Medan Branch.To find out what customers want, PT. Bank Bukopin Medan Branch conducted a customer satisfaction survey , so that it can be seen the degree of customer satisfaction and where the customer dissatisfaction is, this can be an evaluation for Bank Bukopin itself in order to further improve its services